Seasonal Dynamics of Salt Licks and Their Use by Wildlife in Amazonia - Braga-Pereira, Franciany; Peres, Carlos A; Nóbrega Alves, Rômulo Romeu (Ethnobiology and Conservation, 2024)
In certain Amazonian regions, 25% of hunting occurs at salt licks, sites rich in natural minerals often near creeks prone to periodic flooding. Here, animals engage in geophagy for mineral supplementation and detoxification what enables local hunter to observe their behaviour while waiting their target. Our study evaluates seasonal salt lick availability and wildlife usage, using interviews and obtained information on 31 vertebrate species across 56 salt licks in the Central Amazon. While soil and water consumption attract wildlife, species also visit for bathing, predation, and other behaviors. In general, the season with the highest wild species abundance was the receding floodwaters season, because the creeks’ water level decreases and so the salt lick is exposed. Conversely, during the flood pulse, interviewees perceived that the majority of salt licks are not visited by most species because they are often covered by water. Most of the interviewees (74,46%) said that salt licks are one of the main places where they hunt, however the hunting at salt licks is only done during the receding floodwaters season. Our findings shed light on the ecological significance of salt licks in Amazonia and their role in supporting diverse wildlife communities.